2020
DOI: 10.1016/j.ejvs.2019.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Reticulated Platelets as Predictor of Myocardial Injury and 30 Day Mortality After Non-cardiac Surgery

Abstract: WHAT THIS PAPER ADDSThis study shows the additional value of measuring pre-operative young, reticulated platelets (pRP) in patients undergoing major non-cardiac surgery to predict post-operative myocardial injury (PMI) and 30 day mortality. Measuring pRP could identify patients with an increased risk of PMI and 30 day mortality. Future, prospective studies with consequent adjustment of cardiovascular risk management after pRP measurement, should determine the clinical relevance.Objective: A pre-operative marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 48 publications
3
21
0
Order By: Relevance
“…Combining both hematological parameters with known biological plausibility could explain the clinical utility observed in the multivariate Cox regression model. A high count of reticulated platelets, indicative of higher platelet turnover and production, was independently associated with post-CEA myocardial injury and postoperative mortality [30]. An increased platelet count has been shown to be independently associated with mortality in both ischemic heart disease patients and population-based cohorts [31].…”
Section: Discussionmentioning
confidence: 99%
“…Combining both hematological parameters with known biological plausibility could explain the clinical utility observed in the multivariate Cox regression model. A high count of reticulated platelets, indicative of higher platelet turnover and production, was independently associated with post-CEA myocardial injury and postoperative mortality [30]. An increased platelet count has been shown to be independently associated with mortality in both ischemic heart disease patients and population-based cohorts [31].…”
Section: Discussionmentioning
confidence: 99%
“…101 Other investigators found IPF to be a predictor of inflammatory response as well as of myocardial injury and MACE after cardiac or noncardiac surgery. 47,102,103 Altogether, these findings provide evidence of RPs serving as a prognostic biomarker for adverse cardiovascular events in different pathological settings particularly in the cardiovascular field (Table 2).…”
Section: Validation Of Rps As a Prognostic Biomarkermentioning
confidence: 72%
“…In patients undergoing major noncardiac surgery, preoperative increased levels of RPs were associated with a higher 30-day mortality and a higher rate of postoperative myocardial injury [59].…”
Section: Immature Platelets and Cardiovascular Diseasementioning
confidence: 93%